Patrones de comportamiento violento en la conducta normal. - Juárez, Fernando (Acta Colombiana de Psicología, 2000)
In this research violent behavior patterns produced in population with no stablished history of criminal or agressive characteristics are studied. Violent behavior temporal secuencies are analyzed and eight diferents sequencies are identified and typified, in the population, like behavior patterns. The relationship between such behaviors and some presumed associated diary situations and their relationship to several personality traits and styles of thinking are also observed. EPQ personality questionnaire, positive and negative thinking questionnaire ATQ, irrational belief scale BF, socioeconomic questionnaire and a 30 days self-record were used. Results confirm that some patterns, exist in the whole population and that a weak relationship between sincerity, irrational beliefs, job, health, marital status and violent behaviors is also present. Patterns of violent behavior revealed as the most efficiency methodology of clasification.